Tunable High-Performance Microwave Absorption and Shielding by Three Constituent Phases Between rGO and Fe3O4@SiO2 Nanochains - Li, Chao-Qin; Xu, Wei; Ding, Ruo-Cheng; Shen, Xun; Chen, Zhi; Li, Mao-Dong; Wang, Guang-Sheng (Frontiers in Chemistry, 2019)
In order to tune the microwave absorption together with the electromagnetic shielding performance, reduced graphene oxide (rGO) and Fe3O4@SiO2 nanochains are successfully combined with various mass ratio. By properly adjusting the permittivity and permeability derived from different contents of the rGO and Fe3O4@SiO2 nanochains, the rGO/Fe3O4@SiO2 composite with excellent microwave absorption properties is obtained. And due to adding the highly conductive rGO, the desired shielding effectiveness is also achieved. The reflection loss value of -48.34 dB is achieved for the composite with mass ratio of 1:1, and the bandwidth less than -10 dB can reach up to 4.88 GHz with a thickness of 2.0 mm. Moreover, the composite with mass ratio of 4:1 exhibits superior electromagnetic shielding performance as high as 37 dB, which also broaden its application fields. Considering the outstanding microwave absorption and electromagnetic shielding performance, the composite can be employed as a potential multi-functional material.